CROSS-CULTURAL EXPERIENCE OF MATERNAL POSTNATAL DEPRESSION - Roshaidai Mohd Arifin, Siti; Cheyne, Helen (International Journal of Psychosocial Rehabilitation, 2020)
The prevalence of maternal postnatal depression (PND) varies from 0% to 60% globally. This wide variety brings up the issue of whether PND is a universal medical condition or whether it is an idea impacted by cultural and social translations and the labeling of signs and symptoms. The objective of this review was to understand women’s experience of PND in different countries. Studies reporting women’s experiences of PND were searched through databases of CINAHL, PubMed, MEDLINE, PsycINFO, and ASSIA using specific keywords. Articles published between 2006 and 2016 were filtered for inclusion criteria. A total of 27 studies on maternal experience of PND conducted in ten different countries, including America, Canada, South Africa, the United Kingdom, Norway, Australia, New Zealand, Bangladesh, China, and Taiwan, were reviewed. Findings indicated that while women recognized the emotional changes in themselves after their childbirth, they were unable to perceive these as burdensome symptoms, resulting in delayed diagnosis of PND. The issues of cultures and traditions were perceived by Asian women as one of the contributing factors to PND.HCPs were regarded by the women as having a lack of knowledge in supporting mental well-being among postnatal women. Therefore, it is crucial to educate both HCPs and communities to notice and react to women’s depressed feelings. The management of maternal PND should acknowledge the social and cultural element, as many women associated this with the development of PND.